A long and winding road of referrals: investigating the relationship between healthcare and integration for Nairobi's urban displaced - McAteer, Boel; Alhaj Hasan, Salam; Wanyonyi, Jackline (Frontiers in Human Dynamics, 2023)
This article discusses what integration means in the context of forced displacement, focusing in particular on healthcare access of urban displaced people in Nairobi, Kenya. To do so, it uses a mixed dataset of survey data investigating health and healthcare access for displaced and host respondents in Nairobi’s informal settlements Mathare and Kiambiu or Eastleigh South; key informant interviews with healthcare service providers working with displaced people; and finally a case study of a medical pathway taken by a displaced man living in a suburb to Nairobi.. His journey demonstrates that documentation, information and language remain challenges specific to the displaced populations, and the importance of utilising personal support networks, which will not be available to all patients. Notably, this patient’s path to treatment brought him to clinics within Nairobi’s informal settlements, where healthcare access is often inadequate for its own residents, including both locals and displaced. As such, it shows that where an integrated healthcare system falls short, it can be more beneficial for patients to navigate between the national system and support systems provided for urban refugees.